Super Mad at Everything All the Time: Political Media and Our National Anger - Dagnes, Alison (Springer eBooks Political Science and International Studies, 2019)
1. Two Truths -- 2. Upping the Antis: 50 Years of Vilifying Intellectuals, the Government, & the Media -- 3. Money + Tech = Problems: Technological Development, Financial Imperatives, and The Ensuing Media Landscape -- 4. Us vs. Them: Political Polarization and the Politicization of Everything -- 5. Negative Objectives: The Right Wing Media Circle and Everyone Else -- 6. Consequential, Problematic and Perhaps Resolvable